Current status, trend changes, and future predictions of the disease burden of type 1 diabetes kidney disease in global and China - Yang, Qinghua; Jin, Li; Luo, Mingwei; Xie, Shiwei (Frontiers in Endocrinology, 2025)
ObjectiveThis study analyzes the global and China trends in the prevalence, disease burden, and future projections of Type 1 Diabetic Nephropathy (T1DN) over the past three decades, providing data to inform public health policies and clinical interventions.MethodsData from the Global Burden of Disease (GBD) 2021 database were used to analyze the incidence, prevalence, mortality, years lived with disability (YLDs), years of life lost (YLLs), and disability-adjusted life years (DALYs) of T1DN globally and in China from 1990 to 2021. Trend analysis was conducted using R and Joinpoint software, and the ARIMA model was applied to predict future trends in T1DN prevalence for the next 20 years. A significance level of p<0.05 was applied.ResultsGlobally, deaths from T1DN increased from 49,300(95% CI: 39,088-61,207) in 1990 to 94,020 (95% CI: 71,456-119,984)in 2021, with the age-standardized mortality rate remaining stable. DALYs rose from 2,227,518(95% CI: 1,835,372-2,679,207) in 1990 to 3,875,628 (95% CI: 3,062,395-4,845,503) in 2021, though the age-standardized rate slightly decreased. In China, the mortality rate declined significantly, and DALYs decreased, with the age-standardized DALYs dropping from 80.915/100,000(95% CI: 65.121-98.391)to 47.953/100,000(95% CI: 36.9-60.734). Globally, both incidence and prevalence increased, with global incidence reaching 95,140(95% CI: 82,236-111,471) cases and prevalence rising to 6,295,711 (95% CI: 5,459,693-7,114,345)cases. In China, incidence showed a declining trend, but prevalence continued to rise. The ARIMA model forecasts global incidence will reach 115,000 cases, with prevalence reaching 7,000,000 by 2041. In China, incidence is expected to stabilize, while prevalence may increase to approximately 2,500,000 cases.ConclusionThe burden of T1DN is rising globally, especially in terms of prevalence, while China has made progress in reducing mortality and disease burden. However, challenges remain in chronic disease management. Over the next 20 years, global prevalence is projected to continue increasing, while China’s prevalence may stabilize. Targeted interventions for different age groups and genders will be essential in reducing the T1DN burden.